2020
DOI: 10.20527/twj.v6i1.83
|View full text |Cite
|
Sign up to set email alerts
|

Effect of brine time on quality of wet-salted fish

Abstract: Stingrays or Dasyatis sp. was one kind of fishery commodities. This product was perishable, so it required careful handling through the handling process. Fish preservation was an alternative that can be applied. This study aimed to protect the fresh fish quality throughout the handling process before it was processed further. This research method used the wet-salting method. The principle of this method was to keep the product for a long time in brine for 0h (control/fresh fish), 1h, 2h, and 3h. The analysis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Farid et al [19] found that sun-drying of salted Channa striatus at room temperature (27 °C-30 °C) increased its shelf life. Majid et al [20] found that storing of Dasyatis sp., for 1h in brine was the best treatment to yield a firm product.…”
Section: Discussionmentioning
confidence: 99%
“…Farid et al [19] found that sun-drying of salted Channa striatus at room temperature (27 °C-30 °C) increased its shelf life. Majid et al [20] found that storing of Dasyatis sp., for 1h in brine was the best treatment to yield a firm product.…”
Section: Discussionmentioning
confidence: 99%